ISLAMIC DYNAMICS OF SOUTHEAST ASIA: IDEOLOGICAL PROBLEMS - Isman Iskandar (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This article discusses the dynamics of Southeast Asian Islam: The Problem of Salafi Ideology with a focus on the three things described, namely: the problem of radical Salafi ideology, the dynamics of Southeast Asian Muslims and the handling of religious radicalism in Southeast Asia. Radical ideology is developing among Muslims who identify themselves with Salafis, namely Islamic groups or movements that call for a return to the Koran and Hadith. In subsequent developments, it underwent contextualization with various variants. The main Salafi movement is identified with the main agenda of purifying the faith or containing secularism or restoring the Islamic caliphate or a form of resistance to imperialism. The emergence of religious radicalism is a new challenge for Muslims in the midst of international relations. The characteristics of Southeast Asia are considered to be a prototype for the future of a moderate, friendly, tolerant Islam that dialogues with other civilizations. Current social, political, economic and cultural conditions in Southeast Asia have shown that the existence of Islamic communities in this region must be taken into account. Spreading moderate Islam in the Southeast Asian context has similarities with the thoughts of Azumardy Azra (1955), Jamhari Makruf (1965), Rosita Tandos (1975), Zachary Abuza (2010) and many elaborations of the thoughts of Muhammad Sa'id Ramadan al-Buti ( 2013) and of course will contrast with the thoughts of Salafi figures with various variations such as 'Abd al-'Aziz bin Abdullah bin Baz (1999), Sayyid Qutb (1966) Abdullah Yusuf 'Azzam (1989) which tend to be exclusive and closed.